ANALISIS VALUE AT RISK (VAR) DENGAN METODE HISTORIS DAN MONTE CARLO DALAM HARGA SAHAM SUB SEKTOR BANK - Arizal Tursina; Renea Shinta Aminda; Immas Nurhayati (Jurnal Ekonomi dan Bisnis, 2023)
This study aims to determine the results of Value at Risk in the Bank Sub-Sector Stock Prices using the Historical Simulation and Monte Carlo Simulation methods for the 2019-2022 period. This research uses a descriptive quantitative research approach, and the data used is secondary data with data sources coming from www. finance.yahoo.com. The population used in this study were companies whose shares were listed on the Indonesian Stock Exchange (IDX) and companies included in the IDX with a sampling of 5 companies namely BBCA, BTPN, BMRI, BBNI and BBRI Bank Companies. Based on the results of the test analysis, it shows that the company that has the highest risk VaR level in the Historical Method and the Monte Carlo Simulation Method is PT Bank Tabungan Pensiunan Nasional Tbk and the smallest is PT Bank Central Asia Tbk.